bntu jawab nomer 2 yg B kak
![](https://id-static.z-dn.net/files/dc0/5edc7d5f540520667397b606db2c0d99.jpg)
Penjelasan dengan langkah-langkah:
[tex](f \circ g)(x) = {x}^{2} + 3x + 1[/tex]
[tex]g(x) = x + 1[/tex]
[tex] \: [/tex]
Misal.
[tex]x + 1 = a[/tex]
[tex]a + 1 = x[/tex]
[tex]a = x - 1[/tex]
[tex] \: [/tex]
Maka.
[tex]f(x) = {x}^{2} + 3x + 1[/tex]
[tex]f(x) = {(x - 1)}^{2} + 3.(x - 1) + 1[/tex]
[tex]f(x) = {x}^{2} - 2x + 1 + 3x - 3 + 1[/tex]
[tex]f(x) = {x}^{2} + x - 1[/tex]
[tex]f(2) = {2}^{2} + 2 - 1[/tex]
[tex]f(2) = 4 + 1[/tex]
[tex]f(2) = 5[/tex]
[answer.2.content]